Bandwidth Analysis Using Simple Queue Method at Communication and Informatics Department of Palembang City - Frendi, Aquaris; Misinem, . (INTI International University, 2023)
The goal of this research is to execute bandwidth analysis and management so that the bandwidth obtained by each client is distributed evenly at the Department of Information and Communication in Palembang City. This department serves as a computer network linked to an ISP (Internet Service Provider). The issue at the Palembang City Communication and Information Office is the lack of bandwidth control, which causes the internet access speed to fluctuate. As a result, bandwidth management with Mikrotik is required; the bandwidth distribution method is the basic queue method. You may control bandwidth utilization and split bandwidth evenly by implementing bandwidth management utilizing the simple queue approach, and your internet access speed will become consistent.